Increased dystrophin mRNA and protein levels in atrophic skeletal muscles in streptozotocin-induced diabetic rats - Tatsuro Egawa; Shinya Masuda; Katsumasa Goto; Tatsuya Hayashi (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Severe diabetes frequently induces skeletal muscle atrophy, and dystrophin disruption has been implicated in the pathogenesis of skeletal muscle atrophy. We hypothesized that the downregulation of dystrophin expression causes diabetic-induced muscle atrophy, and investigated whether dystrophin mRNA and protein levels are altered in the atrophic muscles of diabetic rats. Rats received a single intravenous injection of streptozotocin (STZ) (45 mg/kg body weight). Slow-twitch soleus and fast-twitch extensor digitorum longus muscles were dissected from each rat 4 or 12 weeks after the STZ injection. The STZ group had significantly higher blood glucose levels and lower body weights than the control group. The relative muscle weight per body weight was also lower in the STZ group than in the control group, and these changes accompanied a reduction in glucose transporter 4. The phosphorylation of Akt Ser473 and p70 S6 kinase Thr389 was lower in the soleus and extensor digitorum longus muscles of the diabetic rats than in those of the control rats. In contrast, dystrophin mRNA and protein expression were higher in the muscles of the diabetic rats than in those of the control rats. A histochemical study showed that the localization of dystrophin did not differ between the muscles of the control and diabetic rats. Our data suggest that the downregulation of dystrophin is not a general characteristic associated with skeletal muscle in diabetes.